Cryopreservation of mature zygotic embryos, shoot bud regeneration, and field establishment of Pinus elliottii var. elliottii x Pinus caribaea var. hondurensis in vitro-derived plants - Ayala, Lilian P.; Luna, Claudia V.; Brugnoli, Elsa Andrea; Espasandin, Fabiana Daniela; Duarte, María José; González, Ana María; Gauchat, Maria Elena; Moncaleán Guillén, Paloma; Sansberro, Pedro Alfonso (Springer Nature, 2025)
The low seed production of the interspecific hybrid Pinus elliottii var. elliottii x Pinus caribaea var. hondurensis restricts its commercial expansion, making it necessary to ensure efficient cryopreservation and a propagation protocol with no genetic variability. Mature zygotic embryos (MZEs) were cultured in Murashige and Skoog (MS) medium containing 6-benzyladenine (BA) and thidiazuron (TDZ). After 45 days in culture, the highest rate of regeneration (86.7 ± 8.8%) and the maximum number of differentiated buds per responsive explant (15.5 ± 2.8) were achieved from explants cultivated on MS with BA and TDZ (0.5 μM each). Cryopreservation of zygotic embryos using a simple desiccation step and a direct immersion into liquid nitrogen did not affect regeneration and would enhance embryo storage duration. Half-strength MS enriched with sucrose (0.09 M) and gelled with gellan gum (4 g L− 1) under forced ventilation culture was used for shoot elongation. Subsequently, 73 ± 6.7% of shoots produced roots after pretreatment with 1.25 mM indole-3-butyric acid solution for 5 min and culture on quarter-strength MS with sucrose (0.045 M). The regenerated plantlets were successfully transferred to ex vitro conditions. The procedure took 160 days and comprised the adventitious bud formation from cryopreserved MZEs, shoot elongation, rooting, and plantlet acclimation. Considering that water deficit is the major strain during forest establishment, a controlled experiment was carried out to determine the competence of plantlets to overcome this stress. Next, field studies assessed the survival rate and growth of 16-month-old plants. Our results indicated that the field performance of tissue-culture-derived plants is similar to seedlings and rooted cutting plants. Additionally, inter-simple sequence repeat marker analysis revealed the genetic uniformity among the in vitro-raised plants, demonstrating the reliability and validity of the procedure. Thus, the developed regeneration and cryopreservation protocol for mature zygotic embryo explants is a valuable alternative for breeding programs and commercial P. elliottii x P. caribaea propagation.